2011
DOI: 10.1038/hr.2010.271
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adiposity, not abdominal subcutaneous fat area, is associated with high blood pressure in Japanese men: the Ohtori study

Abstract: Visceral adiposity is considered to have a key role in cardiometabolic diseases. The purpose of this study is to investigate cross-sectionally the association between intra-abdominal fat area (IAFA) measured by computed tomography (CT) and high blood pressure independent of abdominal subcutaneous fat area (ASFA) and insulin resistance. Study participants included 624 Japanese men not taking oral hypoglycemic medications or insulin. Abdominal, thoracic and thigh fat areas were measured by CT. Total fat area (TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 46 publications
5
20
0
1
Order By: Relevance
“…Although the VAI could be an alternative index to predict HTN, the HTGW phenotype appeared to be a stronger predictor than the VAI. Our findings are consistent with the limited number of cross-sectional studies [1213141516] and a longitudinal study [11] showing that visceral adiposity measured by CT was an independent predictor of HTN. In cross-sectional and cohort studies of Japanese-Americans [111217], visceral adiposity measured by CT, but not the abdominal subcutaneous adipose tissue, was associated with the prevalence and incidence of HTN.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the VAI could be an alternative index to predict HTN, the HTGW phenotype appeared to be a stronger predictor than the VAI. Our findings are consistent with the limited number of cross-sectional studies [1213141516] and a longitudinal study [11] showing that visceral adiposity measured by CT was an independent predictor of HTN. In cross-sectional and cohort studies of Japanese-Americans [111217], visceral adiposity measured by CT, but not the abdominal subcutaneous adipose tissue, was associated with the prevalence and incidence of HTN.…”
Section: Discussionsupporting
confidence: 92%
“…Magnetic resonance imaging and computed tomography (CT) are gold standards for the measurement of visceral fat, but they are not appropriate for epidemiological studies and everyday practice for practical, ethical, and economic reasons. Only limited investigations have examined the association between visceral adiposity measured by CT and the risk of HTN [111213141516171819], with inconclusive results. Some studies showed a significant or borderline significant association [111315161718], whereas others reported no association [19] or an association in women but not men [14].…”
Section: Introductionmentioning
confidence: 99%
“…Imaging modalities such as computed tomography (CT), magnetic resonance imaging (MRI), and ultrasonography may be used to measure both overall body composition and adipose tissue distribution, including distinguishing subcutaneous adipose tissue from VAT, which, as noted, is closely linked to CVD risk. [89][90][91][92][93] Additionally, modalities such as DEXA, bioelectrical impedance analysis (BIA), and air displacement plethysmography (ADP) may be used to assess body composition. These tools measure %BF, which, although not as closely linked to CVD risk as VAT, is still a useful marker of cardiovascular risk.…”
Section: Nonanthropometric Imaging and Other Measuresmentioning
confidence: 99%
“…The Ohtori Study is an ongoing prospective cohort study designed to investigate the relationship of body composition to chronic diseases . It is made up of 1,036 Japanese men ages 25–77 years who visited the Ohtori Health Promotion Center for a medical checkup between December 2005 and April 2010.…”
Section: Methodsmentioning
confidence: 99%